Hubungan Terpaan Media Sosial dan Persepsi Kerentanan dengan Minat Melakukan Tes Kanker Serviks pada Remaja Wanita di Kota Semarang - Riskiastri Prambandari Rachmawati; Sri Herieningsih (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2018)
Cervical cancer is one of diseases that high risk for woman being. Cervical cancer patients from year to year experienced a significant increase. Indonesia there are at least 15,000 women infected with cervical cancer each year. Lack of understanding about the dangers of cervical cancer cause many women who consider themselves will not be affected by cervical cancer so the interest to perform cervical cancer prevention measures are also still low. So it takes effort to promote the danger of cervical cancer and how to prevent it through various media one of them social media that is currently widely used by the community. The purpose of this study is to determine the relationship of exposure of social media and perceptions of susceptibility with interest in cervical cancer testing. The study population is female adolescent who live in Semarang affected by social media exposure about cervical cancer in the last one month. Meanwhile, the sample of research taken many as 60 respondents with age range 18-22 years by using purposive sampling technique. Based on the hypothesis test conducted using Pearson’s correlation or Product Moment correlation analysis it shows that: First, there is a positive relationship between exposure of social media with interest to cervical cancer testing with a significance value of 0.000 and correlation coefficient value of 0,504. This indicates a moderate relationship with the direction of a positive relationship. The higher the exposure to social media, the higher the interest in cervical cancer testing, and vice versa. Second, there is a positive relationship between perceptions of susceptibility with interest in testing cervical cancer with a significance value of 0.001 and a correlation coefficient of 0.447. The closeness of the acquired relationship and the direction of the relationship is positive. This means, the higher the perception of vulnerability the higher the interest in cervical cancer testing, and vice versa. Suggestion given that social media should be able to provide deep information about cervical cancer and prevention of cervical cancer world, so it is expected interest to do cervical cancer prevention action will increase.